At Westonci.ca, we make it easy to get the answers you need from a community of informed and experienced contributors. Get the answers you need quickly and accurately from a dedicated community of experts on our Q&A platform. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
Answer:
The solution set is 1, -3/4
Step-by-step explanation:
(x - 1)(4x + 3) = 0
We can use the zero product property to solve for x
x-1 =0 4x+3 =0
x=1 4x=-3
x = -3/4
The solution set is 1, -3/4
The solutions to the equation (x - 1)(4x + 3) = 0 are x = 1 and x = -3/4.
To solve this, we need to understand that if the product of two factors is zero, then at least one of the factors must be zero. So, we set each factor equal to zero and solve for x:
- x - 1 = 0
Adding 1 to both sides gives us:
x = 1 - 4x + 3 = 0
Subtracting 3 from both sides gives us:
4x = -3
Dividing both sides by 4 gives us:
x = -3/4
Thus, the solutions are x = 1 and x = -3/4. Therefore, the solution set is 1, -3/4.
We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Your questions are important to us at Westonci.ca. Visit again for expert answers and reliable information.